Quality of state evaluation in stomatology during the five year 2007-2012. Universidad Médica de Camagüey. - Ernesto López Cruz; Jacqueline Legañoa Alonso; Lissette Peraza Gutierrez; Eugenio S. Peraza Sanfeliz (Editorial Ciencias Médicas, 2014)
Introduction: The enlargement of enrollment is a challenge in medical education, and the state owned test certifies the competition of the graduate that's why to analyze the quality of the results obtained in these stages becomes necessary. Objective: Assess the quality in the state-owned evaluation during the five year period 2007-2012 in Camaguey's Faculty of Dentistry Method: A descriptive research of the state-owned exam of 384 students in the period 2007-2012 was done. The percentage method, arithmetical mean () and median were utilized. The results of the theoretic state-owned exam of the latter course were related with the academic index of every student. Results: Student's number increase from 36 in the course 2007-2008 up to  146 in the course  2011-2012. In the five year period, the 53,6 % of the students  achieved  excellent marks,  40,9% achieved good marks , 3,9 % achieved pass mark   and the 1,6 %  achieved a  disapproved mark and   corresponded to the two more numerous courses Conclusions: The quality of Excellent is maintained in he five years period, but the arithmetical mean and median in more numerous students' groups tails off.